Seasonal Time Series Analysis on Export Performance of Hawassa Green Wood Flower Production (SARIMA Model) - Zewdie, Mulugeta Aklilu; Yibabe, Yohannes (International Journal of Mathematical Research, 2017)
This study focuses in determining the trend and seasonality export performance of stem rose flower at Hawassa Green Wood based on five year monthly data. The data was obtained from secondary and primary source and includes from January 2006/7 to December 2010/11. Both descriptive and inferential Statistical methods of analysis are used to analyses the data. The analysis is done by using Minitab statistical soft ware. The methods of interests are trend analysis and Box-Jenkins SARIMA models. The trend for this data shows an increasing trend however seasonal fluctuation occurs. SARIMA (0, 1, 2) (0, 1, 1) are the selected Box-Jenkins potential model for this data and by using this model forecasted two years ahead.